Improved bond behavior between GFRP rebar and concrete using calcium sulfoaluminate. (15th June 2016) - Wu, Chao; Bai, Yu; Kwon, Sukmin
Highlights: A practical method to improve the bond between FRP rebar and concrete is proposed. This method relied on the CSA agent at the interface between FRP and concrete. The bond capacity was increased by 41% comparing to the case without CSA agent. The bond of FRP rebar to concrete was even higher than that of steel rebar. Abstract: Glass Fiber Reinforced Polymer (GFRP) rebars have great potential for applications in concrete structures under corrosive environment. The bond behavior between GFRP rebar and concrete needs to be understood for such applications. This paper presents a new method for improving the bond behavior using Calcium Sulfoaluminate (CSA). CSA has an expansive effect when added to the concrete mixture. It is proposed to embed the GFRP rebar in the fresh expansive concrete which is encased by the surrounding hardened concrete. When the fresh expansive concrete gradually becomes hardened, the expansion is restrained by the surrounding concrete, resulting in confining pressure on the GFRP rebar. To validate the proposed method, experimental pull-out tests were conducted to quantify the improved bond behavior between GFRP rebar and concrete. Steel rebar pull-out test was also carried out for comparison purpose. The experimental results were reported including failure modes, ultimate pull-out capacities and bond-slip responses. It was found that the bond behavior between GFRP rebar and surrounding concrete was greatly improved using the proposed method.